Correlation between maternal thyroid function tests and endothelin in preeclampsia-eclampsia - (:unkn) unknown (ELSEVIER SCIENCE INC, 1999)
Objective: To investigate the relationship between results of maternal thyroid function tests and endothelin levels in preeclamptic or eclamptic women. Methods: Thyroid hormones, TSH, and endothelin were measured in plasma or serum from 37 proteinuric, preeclamptic or eclamptic women and 20 normotensive, nonlaboring, pregnant women. Subjects were subdivided into four groups according to hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome and birth weights of infants with respect to gestational age. Results: A significant decrease in concentrations of total thyroxine (T4) (13.76 +/- 1.84 mu g/dL versus 10.00 +/- 1.48 mu g/dL, P <.05), total triiodothyronine (T3) (180.58 +/- 30.84 ng/dL versus 141.16 +/- 27.31 ng/dL, P <.01), free T4 (1.45 +/- 0.27 ng/dL versus 1.10 +/- 0.21 ng/dL, P <.01) and free T3 (3.32 +/- 0.56 pg/mL versus 2.41 +/- 0.60 pg/mL, P <.01) and a significant increase in TSH (1.55 +/- 0.89 mu IU/mL versus 2.96 +/- 1.07 mu IU/mL, P <.05) and endothelin (2.31 +/- 0.61 pg/mL versus 6.11 +/- 1.41 pg/mL, P <.001) levels were observed in the preeclamptic-eclamptic group compared with the normotensive group. Also, women without HELLP syndrome and without small-for-gestational-age infants had elevated levels of thyroid hormones and decreased levels of TSH and endothelin compared with other subgroups, but statistical significance was reached only in total T4 (P <.05), TSH (P <.05), and endothelin (P <.001). Birth weights of infants born to preeclamptic or eclamptic women correlated positively with total T4 (P <.01) and total T3 (P <.01) and negatively with TSH (P <.01) levels. A more significant negative correlation was found in preeclamptic-eclamptics (P <.001) between birth weight and endothelin levels than in control subjects (P <.05). Endothelin levels in preeclamptic or eclamptic women correlated negatively with total T4 (P <.01), total T3 (P <.05), free T4 (P <.05), and free T3 (P <.05) and positively with TSH levels (P <.01) compared with control subjects. Conclusion: Moderate decreases in thyroid hormones with concomitant increases in TSH levels in maternal serum correlated with severity of preeclampsia or eclampsia and high levels of endothelin. Changes in results of thyroid function tests induced by preeclampsia or eclampsia might be consequences of the dysfunction in the hypothalamic-pituitary-thyroid axis, secondary to the disease itself. (Obstet Gynecol 1999;94:551-5. (C) 1999 by The American College of Obstetricians and Gynecologists.).
Keywords: HORMONE CONCENTRATIONS; BIRTH-WEIGHT; PREGNANCIES; LOCALIZATION; WOMEN; SERA; RAT